Postdiagnostic use of antihypertensive medications and survival in colorectal, lung, corpus uteri, melanoma and kidney cancer patients with hypertension - Rūta Everatt; Irena Kuzmickienė; Birutė Brasiūnienė; Ieva Vincerževskienė; Birutė Intaitė; Saulius Cicėnas; Ingrida Lisauskienė (BMC Cancer)
Abstract Background Arterial hypertension is one of the most frequent comorbidities in patients with cancer. Studies have indicated that drugs used to control hypertension may alter cancer patient survival; however, epidemiological findings for their impact on cancer survival remain inconsistent. The aim of this study was to examine the effect of the consumption of antihypertensive (AH) medication on the risk of death in cancer patients. Methods The association between 1-year postdiagnostic AH medication intake and the risk of death was examined in a population-based cohort of cancer patients including colorectal (N = 1104), lung (N = 344), melanoma (N = 334), corpus uteri (N = 832) and kidney cancer (N = 714), diagnosed between 2013 and 2015, and identified from the Lithuanian Cancer Registry. Multivariate Cox proportional hazards models were used to estimate hazard ratios (HRs), and corresponding 95% confidence intervals (95% CI) to assess associations between AH medications and cancer-specific and overall mortality. Results We found a statistically significant decrease in mortality among colorectal cancer patients who were users of angiotensin receptor blockers (ARBs) (HR: 0.68, 95% CI: 0.47–0.98) or angiotensin converting enzyme inhibitors (ACEIs) (HR: 0.69, 95% CI: 0.52–0.91). A higher usage of ARBs and ACEIs was related to further improved colorectal cancer survival (HR 0.62, 95% CI: 0.39–1.00 and HR 0.60, 95% CI: 0.42–0.86, respectively). The subgroup analyses also demonstrated significantly better cancer specific survival in ARB users and ACEI users versus non-users in colorectal cancer patients with adenocarcinoma, surgery treatment, chemotherapy treatment and ARB or ACEI use before diagnosis. The results suggest a lower mortality among colorectal cancer patients with a higher usage of diuretics. Increased cancer-specific mortality was observed among corpus uteri cancer patients using ARBs and among melanoma patients using beta blockers (BBs); however, there was no evidence of consistent statistically significant associations in subgroup analyses. Conclusion This study supports a link between ARB and ACEI use and increased survival among colorectal cancer patients. Further research is needed to provide a detailed evaluation of the effects of AH medications on cancer survival.